Monitoring And Control System Of Industrial Electric Motors Using The Internet Of Things (IoT) - Irvan Hanafi; Fachrudin Hunaini; Diky Siswanto (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
The electric motor plays an important role in an industry as a driver in a particular system, for example, rotating a pump impeller, fan or blower, moving a compressor, and lifting materials. The electric motor is sometimes called the "work horse" of industry. It is estimated that motors use about 70% of the total electrical energy in the industry. In making industrial motor monitoring and control systems using IoT with the blynk application, it works in showing the parameters of voltage, current, temperature, and RPM. The module consists of an electric motor, a DHT11 sensor, a PZEM004T sensor, an RPM sensor, and an ESP 8266 microcontroller. In the research conducted, the system made is capable of monitoring and controlling many modules. So that the overall monitoring and control system of electric motors in the company can be integrated into a system. In testing the voltage sensor with a measuring instrument there is an error value of 0.04%, while the current sensor has an error of 2.5%, followed by temperature testing there is an error of 1.8%. the RPM sensor parameter has a value of 1.17%. Remote manual control can be controlled using a smartphone with the blynk application so that the operator can immediately turn off the motor remotely if there is a problem or damage to the electric motor.